Identifikasi Faktor-Faktor Sosial-Ekonomi Migrasi Tenaga Kerja (Kasus Ibu Rumah Tangga yang Bekerja dari Sektor Pertanian ke Sektor Non Pertanian) - Agus Sumanto (Universitas Negeri Malang, 2009)
Many factors of labor migration from agricultural to non agricultural sector could be accounted for. This research aims to predict what the main factors of such migration phenomenon are for housewife workers in a small district Singosari, Malang regency. There are five factors those directly influence on the migration of housewife workers from agricultural to non agricultural sector: (a) non agricultural wage, (b) household income level, (c) number of family members, (d) educational level, and (e) land area held by household.Keywords: labor migration, non-agricultural wage, household income